Evaluating the service quality of Malaysian Islamic Banks: An importance-performance analysis approach - Mohd Thas Thaker, Hassanudin; Khaliq, Ahmad; Mohd Thas Thaker, Mohamed Asmy (International Business Academics Consortium, 2016)
This study was designed to evaluate the service quality of Malaysian Islamic banking from the customer’s perspective. The primary data was collected by administering survey questions in Klang Valley (Selangor and Kuala Lumpur), and the analysis was conducted using importance-performance analysis (IPA). The results revealed that service quality attributes such as Shariah requirements, reliability, assurance, responsiveness, website efficiency, and tangibility play an important role in determining customer satisfaction with Malaysian Islamic banks. These findings should assist market players, particularly the Malaysian Islamic banking industry, and policy makers in understanding and enhancing customer satisfaction regarding the quality of service offered by the Islamic banking industry in Malaysia. The research findings could also be used as part of the blueprints for market players to draft the necessary policies with regard to service quality of the banking industry.